Religions in World- And Global History: A View from the German-Language Discussion - Nolte, Hans-Heinrich (2015)
The author argues that religious history is underestimated in its importance for World- and Global history. The history of religions is quite often an established sub-discipline within convincing research traditions. In order to reconstruct the past adequately, historians need academically controlled data about the beliefs of the people they are dealing with. This book offers ten examples from a wide range of religious beliefs which show that developments in religion have far reaching consequences for general history ? in the change from Empire to the system of European nations, in establishing social disciplines as part of capitalist societies, in attempts of semi-peripheral states struggling for a place in the European World-System, in defence of Muslim societies on the peripheries and in postcolonial Africa.